Consumption pattern and pH of beverages ingested by Dentistry students - Mejía Pacheco, Daniela; Garcés Ávila, Carolina; Hoyos Hoyos, Vivi; Reales Gutiérrez, Yuranis; Orozco Paéz, Jennifer (Universidad y Salud, 2024)
Introduction: The beverage consumption pattern has changed in recent years due to their accessibility and sociocultural changes. However, their high sugar content and pH represent a risk factor for oral and systemic disorders. Objective: To determine the consumption pattern and pH of beverages ingested by Dentistry university students. Materials and methods: A descriptive cross-sectional study was conducted with 138 students who fulfilled a self-completed survey. The consumption frequency and volume were assessed through a validated instrument, adapted to locally marketed beverages. A portable digital pH meter was used to measure pH and the data were analyzed through descriptive statistics using 2016 Microsoft Excel®. Results: The frequency of beverage consumption was considered occasional, the most common brands being Hit® processed juices (blackberry and tropical) and Postobon® soda (apple). The most common consumed volume was 12 fl oz, being more frequent in the time periods between meals. Conclusion: A high percentage of participants consume processed beverages with a critical pH of <5.5. Their frequent consumption represents a risk factor for oral diseases.